Elevated Random Luteinizing Hormone is an Unreliable Indicator for Pubertal Suppression in Girls Treated with Monthly Leuprolide for Idiopathic Central Precocious Puberty - Pattara Wiromrat; Ouyporn Panamonta (JCRPE, 2019)

(untitled)
Objective:Longitudinal data regarding random luteinizing hormone (LH) concentrations in patients with idiopathic central precocious puberty (ICPP) during treatment are limited. Therefore, we sought to evaluate random LH and estradiol concentrations during monthly leuprolide injection and their associations with pubertal progression and final adult height (FAH) in girls with ICPP.Methods:Medical records of 27 girls with ICPP who had attained FAH were reviewed. Patients’ height, weight, Tanner stage, growth rate (GR), bone age, random LH measured by both immunoradiometric and immunochemiluminescent methods, follicular-stimulating hormone (FSH) and estradiol levels were monitored until FAH.Results:Treatment was started at a mean (±standard deviation) age of 8.1±0.6 years with mean duration of 3.9±0.2 years. At six months of follow-up, random LH (p=0.048), FSH (p<0.001) and estradiol (p=0.023) concentrations were decreased compared with baseline. Thereafter, random LHs were well suppressed. GRs gradually decreased to prepubertal norm by month 12. Seventeen patients (63%) exhibited pubertal LH concentrations at least once during treatment visits. Furthermore, 43 of a total 116 (37%) LH measurements were found elevated. However, those patients with elevated random LH did not show signs of pubertal progression. After treatment, mean FAH was greater than predicted adult height (p<0.0001) and target height (p=0.03). At no time points of treatment did random LH, FSH and estradiol correlate with GRs or FAH.Conclusion:Elevated random LH is commonly found in ICPP girls during monthly leuprolide treatment. However, these elevations were not associated with clinical progression of puberty or decreased FAH, suggesting that it is not a reliable method for CPP monitoring.